Differentiated pattern of complement system activation between MOG-IgG-associated disease and AQP4-IgG-positive neuromyelitis optica spectrum disorder - Cho, Eun Bin; Min, Ju-Hong; Waters, Patrick; Jeon, Miyoung; Ju, Eun-Seon; Kim, Ho Jin; Kim, Su-Hyun; Shin, Ha Young; Kang, Sa-Yoon; Lim, Young-Min; Oh, Sun-Young; Lee, Hye Lim; et al. (Frontiers in Immunology, 2024)
Background: Myelin oligodendrocyte glycoprotein antibody (MOG) immunoglobulin G (IgG)associated disease (MOGAD) has clinical and pathophysiological features that are similar to but distinct from those of aquaporin-4 antibody (AQP4-IgG)-positive neuromyelitis optica spectrum disorders (AQP4-NMOSD). MOG-IgG and AQP4-IgG, mostly of the IgG1 subtype, can both activate the complement system. Therefore, we investigated whether the levels of serum complement components, regulators, and activation products differ between MOGAD and AQP4-NMOSD, and if complement analytes can be utilized to differentiate between these diseases.The sera of patients with MOGAD (from during an attack and remission; N=19 and N=9, respectively) and AQP4-NMOSD (N=35 and N=17), and healthy controls (N=38) were analyzed for C1q-binding circulating immune complex (CIC-C1q), C1 inhibitor (C1-INH), factor H (FH), C3, iC3b, and soluble terminal complement complex (sC5b-9).In attack samples, the levels of C1-INH, FH, and iC3b were higher in the MOGAD group than in the NMOSD group (all, p<0.001), while the level of sC5b-9 was increased only in the NMOSD group.In MOGAD, there were no differences in the concentrations of complement analytes based on disease status. However, within AQP4-NMOSD, remission samples indicated a higher C1-INH level than attack samples (p=0.003). Notably, AQP4-NMOSD patients on medications during attack showed lower levels of iC3b (p<0.001) and higher levels of C3 (p=0.008), C1-INH (p=0.004), and sC5b-9 (p<0.001) compared to those not on medication. Among patients not on medication at the time of attack sampling, serum MOG-IgG cell-based assay (CBA) score had a positive correlation with iC3b and C1-INH levels (rho=0.764 and p=0.010, and rho=0.629 and p=0.049, respectively), and AQP4-IgG CBA score had a positive correlation with p=0.003).Conclusions: This study indicates a higher prominence of complement pathway activation and subsequent C3 degradation in MOGAD compared to AQP4-NMOSD. On the other hand, the production of terminal complement complexes (TCC) was found to be more substantial in AQP4-NMOSD than in 5 MOGAD. These findings suggest a strong regulation of the complement system, implying its potential involvement in the pathogenesis of MOGAD through mechanisms that extend beyond TCC formation.